2019
DOI: 10.3389/fpls.2019.00108
|View full text |Cite
|
Sign up to set email alerts
|

The Fusion Activity of IM30 Rings Involves Controlled Unmasking of the Fusogenic Core

Abstract: The inner membrane-associated protein of 30 kDa (IM30, also known as Vipp1) is required for thylakoid membrane biogenesis and maintenance in cyanobacteria and chloroplasts. The protein forms large rings of ∼2 MDa and triggers membrane fusion in presence of Mg2+. Based on the here presented observations, IM30 rings are built from dimers of dimers, and formation of these tetrameric building blocks is driven by interactions of the central coiled-coil, formed by helices 2 and 3, and stabilized via additional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 61 publications
(123 reference statements)
5
37
0
Order By: Relevance
“…The core structure of IM30 proteins is the coiled-coil formed by the helices and 3 15,19,30,31 . This structure is stable even in the isolated, monomeric helix 2-3a fragment 30 ; thus, no additional interactions with other parts of the protein are required for secondary and tertiary structure formation of this fragment. In contrast, the isolated C-terminal region comprising helix 3b-7 is largely unstructured, albeit capable of forming stable dimers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The core structure of IM30 proteins is the coiled-coil formed by the helices and 3 15,19,30,31 . This structure is stable even in the isolated, monomeric helix 2-3a fragment 30 ; thus, no additional interactions with other parts of the protein are required for secondary and tertiary structure formation of this fragment. In contrast, the isolated C-terminal region comprising helix 3b-7 is largely unstructured, albeit capable of forming stable dimers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we recently observed that the isolated helix 2/3 coiled-coil does have an intrinsic propensity to dimerize 30 but does not form higher-ordered super-complexes. Thus, interactions involving both, the helix 2-3 coiled-coil as well as (at least) the region containing helices 4-6, are required for ring formation 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a fraction of the protein is attached to the chloroplasts' inner envelope or the cyanobacterial cytoplasmic membrane, as well as to thylakoid membranes (TMs) (4)(5)(6)(7). The activity of IM30 is broadly linked to the biogenesis/maintenance of TMs (recently reviewed in (8)), and two specific activities are currently studied and discussed in greater detail: (i) membrane protection (9)(10)(11)(12)(13)(14)(15) and (ii) membrane remodeling and repair (10,15,16). Protection and maintenance of the TM system are necessary to prevent energy dissipation and to maintain a proton gradient across the TM, a membrane system highly vulnerable to membrane damage (17).…”
mentioning
confidence: 99%